Gender Equality Capacity of Administrative Council Members in a State University and Local Universities And Colleges - M. Rodriguez, Maria Teresa; S. Tan, Consorcia; Buenvinida, Lerma P.; P. Lapie, Lustina (International Journal of Scientific Research and Management (IJSRM), 2021)
The study determines the academic leadership capabilities, administrative creativity and gender equality capacities of administrative council members of a state university and local colleges in the province of Laguna, Philippines. The respondents were members of the university/college administrative council. In terms of administrative functions, many are chairpersons or coordinators while some are in the higher position like campus directors and vice-presidents. Findings revealthat there is a positive and significant relationship between the following subscales of academic leadership and gender equality capacity: cognitive capability and programmes, change - oriented capability and programmes, skills and processes; role-specific and programmes and operations Further, it was observed that leadership performance is positively and highly significantly related to all subscales of gender equality capacity. Meanwhile, there is a highly significant relationship between respondent’s administrative creativity and gender equality in terms of skills and processes. This implies that the more creative the administrative council members, the more confident in their gender equality capacity in terms of skills and processes. Majority of the respondents   experienced training or orientation on gender issue   and have taken gender related courses in the last two years. However, most of them are not satisfied with the training. Hence it is recommended that the local colleges and university need to conduct seminars and trainings to enhance the awareness of the officials and other constituents on gender sensitivity.